Revisiting the Britain-US-Turkey triangle during the transition from Pax Britannica to Pax Americana (1947-1957). Issue 4 (1st October 2020) - Barlas, Dilek; Yılmaz, Şuhnaz; Güvenç, Serhat
ABSTRACT: This article analyses the triangular relations between Britain, the United States and Turkey in the volatile Middle East and Eastern Mediterranean region at the advent of the Cold War. It examines the political, economic and military strategies that enabled Turkey to adapt to the transitional period from the Pax Britannica to the Pax Americana (1947–1957) in the Middle East and the Eastern Mediterranean. By focusing on this turbulent decade extending from the Truman Doctrine (1947) to the Eisenhower Doctrine (1957), this study posits that the transition from the waning influence of Britain to the coalitional hegemony of the United States was protracted and multi-layered. In this context, Turkey had to walk a diplomatic tightrope while managing certain aspects of continuity and change in a volatile region.